2022
DOI: 10.1007/s10143-022-01875-4
|View full text |Cite
|
Sign up to set email alerts
|

Decompression with or without fusion in degenerative adjacent segment stenosis after lumbar fusions

Abstract: Adjacent segment stenosis can occur after lumbar fusion surgery, leading to significant discomfort and pain. If further surgeries are required, the choice of the operative technique is an individual decision. In patients without over instability, it is still uncertain whether patients with adjacent spinal stenosis should be treated like primary lumbar spinal stenosis via decompressive surgery alone or with decompression and fusion. This is a retrospective analysis with prospective collected data. We included p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These findings have been recently corroborated in the literature by multiple studies. 25 , 27 , 28 Once again, ChatGPT presented a conservative recommendation to this question and emphasized that only patients that present with instability tend to get this operation. However, it once again presented within its response fictitious papers that could not be found in the literature.…”
Section: Assessment Of Chatgpt’s Performancementioning
confidence: 99%
“…These findings have been recently corroborated in the literature by multiple studies. 25 , 27 , 28 Once again, ChatGPT presented a conservative recommendation to this question and emphasized that only patients that present with instability tend to get this operation. However, it once again presented within its response fictitious papers that could not be found in the literature.…”
Section: Assessment Of Chatgpt’s Performancementioning
confidence: 99%
“…Therefore, Palejwala et al reserve minimally invasive surgery (MIS) decompression alone for patients whose likelihood of developing instability is low (e.g., no spondylolisthesis or significant malalignment) 53 . This is supported by Früh et al, who retrospectively compared microsurgical decompression with decompression and fusion for patients with adjacent segment stenosis without instability, deformation, and neuroforaminal stenosis 55 . Both groups benefitted from surgical intervention with no difference in complication rates, suggesting that in patients, decompression may not be inferior to compression and fusion.…”
Section: Treatmentmentioning
confidence: 82%
“…Orita et al [4] reported that, during an average follow-up of 13.3 months after floating fusion surgery, adjacent L5-S1 foraminal stenosis was found in eight of 125 patients (6.4%). Adjacent level foraminal stenosis is one of the primary causes of intractable radiculopathy after fusion surgery [9][10][11].…”
Section: Introductionmentioning
confidence: 99%